Paris Conference between the representatives of the major states of the armies of the Little Entente and France on the subject of liaisons and transmissions (1936) - Nicolescu, Andrei (Technium Social Sciences Journal, 2023)
Apart from some high-level mission visits, we cannot record any contacts with a concrete agenda between representatives of the major French, Romanian or Little Entente states for the years 1930-1936. An exception was the Paris Conference between the military representatives of the Little Entente and those of France, held between 14th and 16th of December 1936, with the aim of signing an "Agreement concerning the organisation and functioning of liaisons between the General Headquarters of the Little Entente and France in the event of mobilisation or political tensions".